Assessment of Happiness Index among Higher Education Teaching Faculty Using Analytic Hierarchy Process (AHP) - Dr.G.Uma Maheswari (International Conference on Multidisciplinary Research Perspective, 2025)
The well-being of teaching faculty is crucial for sustaining the quality of higher education. This study evaluates the Happiness Index of higher education faculty using a structured multi-criteria decision-making approach based on the Analytic Hierarchy Process (AHP). Key determinants of faculty happiness—work-life balance, institutional support, interpersonal relationships, compensation and benefits, recognition, and personal growth—were identified and prioritized through expert evaluations and faculty surveys. Pairwise comparisons and AHP computations determined the relative weights of each factor, and consistency ratios were verified for reliability. Results revealed that work-life balance and institutional support are the most influential drivers of faculty happiness, followed by recognition and interpersonal relationships. The resulting composite Happiness Index quantitatively represents faculty satisfaction and overall organizational well-being. This methodological framework provides actionable insights for policymakers and administrators to formulate strategies that enhance faculty happiness, teaching effectiveness, and institutional climate